2011
DOI: 10.3892/ijo.2011.1089
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from the lung carcinoma antigen, Lengsin

Abstract: Abstract.Lengsin is an eye lens protein with a glutamine synthetase domain. We previously identified this protein as a lung carcinoma antigen through cDNA microarray analysis. Lengsin protein is overexpressed irrespective of the histological type of lung carcinoma, but not in normal tissues other than the lens. Therefore, to significantly extend the use of Lengsinbased T-cell immunotherapies for the treatment of patients with lung carcinoma, we searched for HLA-A * 0201-restricted epitopes from this protein by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…LGSN , located on chromosome 6q12, encodes a glutamine synthetase I family protein, called lengsin, that was previously reported to be a constitutive lens‐specific protein but without the glutaminase activity . Recently, lengsin was identified as a novel tumor‐associated antigen and revealed its essential role in cell survival . In the present study, we found that CM patients with genotypes of LGSN rs12663017 TA + AA had a better CMSS.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…LGSN , located on chromosome 6q12, encodes a glutamine synthetase I family protein, called lengsin, that was previously reported to be a constitutive lens‐specific protein but without the glutaminase activity . Recently, lengsin was identified as a novel tumor‐associated antigen and revealed its essential role in cell survival . In the present study, we found that CM patients with genotypes of LGSN rs12663017 TA + AA had a better CMSS.…”
Section: Discussionsupporting
confidence: 60%
“…42 Recently, lengsin was identified as a novel tumor-associated antigen and revealed its essential role in cell survival. 42,43 In the present study, we found that CM patients with LGSN rs12663017, and (c) NOXRED1 rs8012548 in the additive model; (B) the eQTL from the GTEx project using the additive model for HAL rs17676826 in skin tissues from sun-exposed lower leg skin (a) and sun-not-exposed suprapubic (b), NOXRED1 rs8012548 in skin tissues from sun-exposed lower leg (c), and sun-not-exposed suprapubic (d), LGSN rs12663017 in the whole blood (e), and NOXRED1 rs8012548 in subcutaneous adipose (e family. 44 In general, glutamine is degraded to glutamate, which then can consecutively be converted to proline by PYCR.…”
Section: Discussionmentioning
confidence: 99%
“…2) suggested that mGPC3-1 could induce peptide-specific CTLs. In addition, antigen-derived and CTL-inducible peptides are not necessarily presented by cancer cells endogenously expressing the antigen (23,30). Hence, we confirmed whether the mGPC3-1 peptide-specific CTL line could recognize RMA-GPC3-puro endogenously expressing mGPC3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the binding affinity of the predicted peptides to H2-K b or H2-D b molecules, an in vitro cellular binding assay was performed as previously reported (23,26). Briefly, after incubation of RMA-S cells in culture medium at 26°C overnight, cells (1×10 6 ) were washed with PBS and suspended in 100 μ l Opti-MEM ® (Invitrogen) with or without 10 μ g peptide, followed by incubation at 26°C for 3 h and then at 37°C for 3 h. After washing with PBS, H2-K b or H2-D b expression was measured with a BD FACSCanto™ II flow cytometer (BD) using FITC-conjugated H2-K b (BioLegend Inc., AF6-88.5) or H2-D b (BioLegend Inc., KH95) specific monoclonal antibody and mean fluorescence intensity (MFI) was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Activated CTLs play an important role in the antitumor immunological response by specifically recognizing and subsequently killing tumor cells expressing TAAs (1,2). Dozens of TAAs have been newly identified and well described in recent years (3)(4)(5)(6). However, the expression of most TAAs are restricted to a few tumor types and to a fraction of patients with these types of tumors (7)(8)(9)(10), and the appearance of antigen-loss or antigen-alteration mutations in tumor cells in response to immune pressure has also been highlighted and extensively elucidated by many researchers (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%